Policy Implications of Ageing Sexualities - Heaphy, B; Yip, A.K.T. (Cambridge University Press, 2006)
This article aims to open up debate on the policy implications of ageing sexualities. The article begins by discussing the heteronormative perspective that frames current discourse on older people’s needs and citizenship. It then presents data from an empirical study to highlight the concerns that older lesbians and gay men have about housing, health and social service provision, work and job security, and relationship recognition. The article illustrates how the heterosexual assumption that informs policy making can limit the development of effective strategies for supporting older lesbians and gay men; and raises broader questions about policy making, social inclusion and citizenship.